Analisis Litofasies dan Lingkungan Pengendapan Formasi Nanggulan Lintasan Kali Songgo, Kabupaten Kulon Progo - Hani, Delvina Syaifira Norma; Rizqi, Al Hussein Flowers; Pandita, Hita (ReTII, 2020)
The Nanggulan Formation has a very narrow spread compared to other formations. In Kulon Progo formation has the oldest age in the Middle Eocene-Early Oligocene. This research is located on the Songgo River at coordinates 07 Â° 44 ’00.7 "S - 110 Â° 12’ 17.5" E to 07 Â° 44 ’15.3 "S - 110 Â° 11’ 53.6" E. This research intends to reveal the types of depositional environments that are developed along the Kali Songgo track using measured stratigraphic log analysis. The stratigraphic log’s interpretation indicated lithofacies, facies associations, and the depositional environment. The lithofacies that compiled the research location based on lithological data and sedimentary structure can be divided into ten types: a.Bedded claystone, b.Laminated sandstone, c.Cross-bedding sandstone, d.Bedded sandstone, e.Bedded siltstone, f.Massive claystone, g.Laminated siltstone, h.Graded-bedding sandstone, i.Wavy sandstone, and j.Massive sandstone. Three facies associations are recognized based on the lithofacies grouping: 1. Mud flats, 2. Mixed flats, and 3. Sand flats. The depositional environment that developed along Kali Songgo track was Tidal flats.